2007
DOI: 10.1016/j.chom.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Cowpox Virus Exploits the Endoplasmic Reticulum Retention Pathway to Inhibit MHC Class I Transport to the Cell Surface

Abstract: Major histocompatibility complex (MHC) class I molecules assemble with peptides in the ER lumen and are transported via Golgi to the plasma membrane for recognition by T cells. Inhibiting MHC assembly, transport, and surface expression are common viral strategies of evading immune recognition. Cowpox virus, a clinically relevant orthopoxvirus, downregulates MHC class I expression on infected cells. However, the viral protein(s) and mechanisms responsible are unknown. We identify CPXV203 as a cowpox virus prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…The complete alignment was done upon these sequences, and showed that all of these homologues contain the ER retrieval signal KDEL or RDEL. These tetrapeptides are responsible for the retention of proteins in the ER lumen (Munro & Pelham 1987;Persson et al 2005;Byun et al 2007), which suggested that BmGRP78 is an ERlocalized protein.…”
Section: Homology Analysis Of Bmgrp78mentioning
confidence: 99%
“…The complete alignment was done upon these sequences, and showed that all of these homologues contain the ER retrieval signal KDEL or RDEL. These tetrapeptides are responsible for the retention of proteins in the ER lumen (Munro & Pelham 1987;Persson et al 2005;Byun et al 2007), which suggested that BmGRP78 is an ERlocalized protein.…”
Section: Homology Analysis Of Bmgrp78mentioning
confidence: 99%
“…Because CPXV has coevolved with its rodent hosts, CPXV infection of rodents is appropriate for study of orthopoxvirus-host interactions. Two endogenous viral proteins, CPXV12 and CPXV203, act synergistically to down-regulate MHC class I molecules during CPXV infection (12)(13)(14). CPXV12 binds to the peptide-loading complex and inhibits loading of optimal peptides, whereas CPXV203 retains fully assembled MHC class I molecules in the ER by hijacking the KDEL receptor-ER retention pathway.…”
Section: D8mentioning
confidence: 99%
“…CPXV has the largest genome in the orthopoxvirus genus (34) and contains several ORFs not found in either the VV or ECTV genome. This includes two ORFs, CPXV012 and CPXV203, that potently down-regulate the expression of MHC class I (35)(36)(37)(38). Although this might render the infected cell sensitive to NK cell-mediated lysis, CPXV also encodes another ORF, CPXV018, that binds in vitro with high affinity to the NKG2D activation receptor and blocks its recognition of ligands on target cells (39).…”
Section: Significancementioning
confidence: 99%